2004
DOI: 10.1021/ic0400641
|View full text |Cite
|
Sign up to set email alerts
|

The Renaissance of Aluminum Chemistry

Abstract: The preparation and reactions of stable monomeric and tetrameric organoaluminum(I) compounds are described. Especially, their conversion to the more stable oxidation state (III) is discussed. The synthesis of unusual and unique molecules such as LAl(OH)(2), LAl(SH)(2), LAl(SeH)(2), and LAl(NH(2))(2) is reported. A new synthetic approach to organometallic hydroxides and amides was discovered, when N-heterocyclic carbenes are used as hydrogen chloride acceptors. The synthesis of LGeOH demonstrates that this meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(53 citation statements)
references
References 59 publications
1
51
0
1
Order By: Relevance
“…[14] Starting from the basic molecule of N-aryl-NЈ-benzoylthiourea, a number of derivatives have been synthesized and structurally characterized with varying aryl rings typically modified by methyl, [15] carboxyl, [16] phenyl, [17] hydroxyl, [18] trifluoromethyl, [19] ferrocenoyl, [10,20] and halide [21] substituents. However, the isopropyl group, which has been used as a bulky group in a number of ligand systems, [22] was not so common in acylthiourea derivatives. [12] Previous work with β-diketiminato ligands has shown that the substituent effect on the synthesis of dialuminoxanes is of principal importance.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Starting from the basic molecule of N-aryl-NЈ-benzoylthiourea, a number of derivatives have been synthesized and structurally characterized with varying aryl rings typically modified by methyl, [15] carboxyl, [16] phenyl, [17] hydroxyl, [18] trifluoromethyl, [19] ferrocenoyl, [10,20] and halide [21] substituents. However, the isopropyl group, which has been used as a bulky group in a number of ligand systems, [22] was not so common in acylthiourea derivatives. [12] Previous work with β-diketiminato ligands has shown that the substituent effect on the synthesis of dialuminoxanes is of principal importance.…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits diverse reactivity patterns with the variation of aluminum hydrides as well as its interacted substrate sources [1][2][3][4][5][6][7], and thus attracts particular interest. The use of AlH 3 ·NMe 3 or dialkylaluminum hydrides as precursors to react with unsaturated molecules, such as alkynes [8][9][10][11][12][13], nitriles, and isonitriles [14][15][16][17], has led to the formation of unique classes of carbaalane, imidoalane, and carbaamidoalane clusters. Several different reaction mechanisms have been suggested and discussed with respect to the highly aggregated forms of the hydroalumination products.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the formation of highly aggregated alane clusters using simple aluminum hydrides [8][9][10][11][12][13][14][15][16][17], such lower aggregation products are available when the reactive aluminum hydrides are stabilized by the sterically demanding ligands [19,20]. This may offer a better understanding on the reaction pathways and further the interaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum compounds with Al in the formal oxidation state (+3) are Lewis acids [27] whereas Al in oxidation state (+1) has a dual behaviour and can act as a Lewis base and Lewis acid [28][29][30]. This property of the latter compound has been postulated based on the results of the ab initio calculations on the [LAl] species [31] [L = HC{(CMe)(2,6-iPr 2 C 6 H 3 N)} 2 ].…”
Section: Janus-faced Aluminummentioning
confidence: 99%